The effect of rose water aromatherapy on breastfeeding womenꞌs sleep quality in early Puerperium period: A ranodmized clinical trial - Hadis Fattah; Katayoun Vakilian; Mahtab Attarha (Mashhad University of Medical Sciences, 2021)
Introduction: Most women experience some degree of sleep disorder during the postpartum period. Since rose water essence is effective in depression, nervous tension and drowsiness, this study was performed with aim to investigate the effect of rose water aroma on the quality of sleep in breastfeeding women. Methods: In this randomized clinical trial study, 84 women at the puerperium period who referred to the five selected health centers in Arak in 2019 were studied. Aromatherapy with rose water essence was performed for three nights in the intervention group. The control group didn't receive any intervention. Sleep quality was collected in the two groups before and at the end of the study by the Pittsburgh questionnaire. Data were analyzed by SPSS software (version 21) and independent paired t, covariance and chi-square tests. P <0.05 was considered statistically significant. Results: After the intervention group, sleep quality increased in the aromatherapy group)p<0.05), while in the control group, the quality of sleep did not change before and at the end of the study (0.824) . Also, at the end of the study, sleep quality significantly increased in the intervention group compared to the control group (p<0.05). Conclusion: It seems that women's sleep quality during puerperium period improved with rose water aromatherapy. Therefore, the use of rose water aromatherapy during lactation is recommended to improve the sleep quality of women during puerperium period.